Integral bridges a fundamental approach to the time-temperature loading problem - England, George L. (Thomas Telford, 1990)
The Highways Agency standard now requires, where possible, that all new bridges with a length of less than 60 metres should be of integral form. In addition, it has been found that, due especially to the problems and costs associated with failed expansion joints, integral bridges are not only cost effective but also have a longer lifespan.